2023
DOI: 10.3390/biology12040601
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnologically Engineered Plants

Abstract: The development of recombinant DNA technology during the past thirty years has enabled scientists to isolate, characterize, and manipulate a myriad of different animal, bacterial, and plant genes. This has, in turn, led to the commercialization of hundreds of useful products that have significantly improved human health and well-being. Commercially, these products have been mostly produced in bacterial, fungal, or animal cells grown in culture. More recently, scientists have begun to develop a wide range of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 188 publications
0
0
0
Order By: Relevance
“…Since the first discovery in the late 1980s that tobacco mosaic virus (TMV) coat protein (CP) confers resistance to the cognate virus in transgenic tobacco plants, a new avenue for virus disease control has been provided [40]. Virus CP-mediated resistance has been found to be highly effective for many different plants against several different viruses [41]. Subsequent studies have shown that the mechanisms underlying CP-mediated virus resistance could differ from one plant virus system to another.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first discovery in the late 1980s that tobacco mosaic virus (TMV) coat protein (CP) confers resistance to the cognate virus in transgenic tobacco plants, a new avenue for virus disease control has been provided [40]. Virus CP-mediated resistance has been found to be highly effective for many different plants against several different viruses [41]. Subsequent studies have shown that the mechanisms underlying CP-mediated virus resistance could differ from one plant virus system to another.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, pharmaceuticals are still produced preferably in bacterial and mammalian cell factories, as fermentation processes are better established and characterized. The complexity and toxicity of new pharmaceuticals might however push these production systems beyond their capabilities and a shift towards plant biofactories might occur in the near future (Buyel, 2019;Narayanan and Glick, 2023).…”
Section: Plant Biofactoriesmentioning
confidence: 99%